2018
DOI: 10.1164/rccm.201709-1908oc
|View full text |Cite
|
Sign up to set email alerts
|

Initial Inflammatory Profile in Community-acquired Pneumonia Depends on Time since Onset of Symptoms

Abstract: Time since symptom onset modifies the systemic inflammatory profile at CAP diagnosis. This information has relevant clinical implications for management, and it should be taken into account in the design of future clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 42 publications
0
37
0
Order By: Relevance
“…A study looked at 541 patients who presented to the emergency department with CAP and were differentiated into early presenters (< 3 d since onset of symptoms) and late presenters (> 3 d). Results showed that CRP and PCT were lower in patients who were early presenters suggesting that time to presentation may affect the interpretation of these biomarkers [28] .…”
Section: Pctmentioning
confidence: 99%
“…A study looked at 541 patients who presented to the emergency department with CAP and were differentiated into early presenters (< 3 d since onset of symptoms) and late presenters (> 3 d). Results showed that CRP and PCT were lower in patients who were early presenters suggesting that time to presentation may affect the interpretation of these biomarkers [28] .…”
Section: Pctmentioning
confidence: 99%
“…Factors, such as the time elapsed since the onset of symptoms, influence CRP kinetics. CPR is more useful in evaluating the inflammatory response of patients at three or more days since the onset of symptoms, because, within the first 48 h, their levels are still raising [116]. Finally, CRP may be useful for cardiovascular risk assessment in healthy women [117].…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…Interferon gamma, a molecule synthesized in the inflammatory immune response against viral infection, inhibits its synthesis, and therefore their levels are low in these infections. Due to its rapid kinetic in CAP patients within the first 48 h since the onset of CAP symptoms, PCT levels are more useful than CRP that is still mounting [116].…”
Section: Procalcitoninmentioning
confidence: 99%
“…Given its widespread availability, it has been validated as a point-of-care (POC) lab test to guide antibiotic use in primary care [54], and levels have been correlated to disease severity and complications in community-acquired pneumonia [55]. Used with other inflammatory marker profiles, CRP may be used to pinpoint the time of infection: In patients who present within 3 days of disease onset, CRP was low, but in patients who present after more than 3 days of symptom onset, CRP levels rose significantly [56].…”
Section: C-reactive Proteinmentioning
confidence: 99%